PENGARUH LATIHAN DAN PUASA TERHADAP HIDRASI - Noverindia, Syarifah Citra; Samodra, Y Touvan Juni; Supriatna, Eka (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2024)
The purpose of this study was to determine the effect of fasting, weight training in the form of circuits in relation to hydration. The research subjects used were students of Sports Coaching Education who took part in fitness activities, totaling 20 people, of the total subjects being sampled with fasting conditions, totaling 10 people. The method used in this research is a single subject research experiment. The instrument in this study was a scale. Data analysis used graphic design A-B-A single subject design. The results showed that there was a decrease in body weight from before doing the exercise and after doing the exercise. The results of the average body weight before doing exercise 5.3 and body weight after doing exercise 5.2 where these results indicate an influence on hydration status. It can be concluded that there is an effect on hydration status that causes weight loss when doing circuit training in a fasting condition.